Semantic network representation of female related issues from the Holy Quran - Ku-Mahamud, Ku Ruhana; Ahmad, Faudziah; Mohamed Din, Aniza; Wan Ishak, Wan Hussain; Ahmad, Farzana Kabir; Din, Roshidi; Che Pa, Noraziah (2012)
Quran is the main source of knowledge and has been a major source reference for all types of problems.Female is one of terms that are very popular in the Quran.This term represents a group of human that are venerable in the aspect of social and family.Quran contains many important issues related to the female. However understanding the issues and the solution from the Quran is difficult due to lack of understanding of Quran literature.Furthermore, female has been addressed in the Quran through several other terms such as women,lady and girls depending on the issues that being addressed.In this paper, 16 terms that are related to female and its related surah and verse have been identified.Semantic network is used to represent the issues. This study also found that, semantic network representation provide a clear and brief overview of the issue that is easy to understand and comprehend.